Influence Of Integrated Learning Models Type Connected Assisted Media Images On Results Learning Of Sains - Nurjannah Nurjannah (Prodi PGSD FIP UNM, 2018)
This study aims to determine differences in the learning outcomes of Sains between students who were taught using integrated learning model connected type of image media with students who were taught using direct instruction model (direc instruction). The population of this study is all students of grade IV SD 237 Mattirobulu Pinrang District 2017/2018 lessons year, which amounted to 186 people. Class samples from this research are 28 students of class IVA as the experimental class and students of grade IVB SD Negri 237 Mattirobulu Pinrang District as many as 28 people as a control class selected by drawing. The research design used is a quasi experimental research design with